2017
DOI: 10.1002/adfm.201703711
|View full text |Cite
|
Sign up to set email alerts
|

3D Foam Strutted Graphene Carbon Nitride with Highly Stable Optoelectronic Properties

Abstract: Controlled morphology modulation of graphene carbon nitride (g-C 3 N 4 ) is successfully realized from bulk to 3D loose foam architecture via the blowing effect of a bubble, which can be controlled by heating rate. The loose foam network is comprised by spatially scaffolded few-atom-layer interconnected flakes with the large specific surface area, as supporters to prevent agglomeration and provide a pathway for electron/phonon transports. The photocatalytic performance of 3D foam strutted g-C 3 N 4 toward RhB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 50 publications
2
52
0
Order By: Relevance
“…7 (a-c) The normalized PL emission spectra of the CN indicate the formation of graphite structure in bulk g-C 3 N 4 . 20,45,46 The melamine has two ngerprint peaks located at around 675 cm À1 (triazine ring breathing mode) and 1558 cm À1 (NH 2 bending mode), respectively. 47,48 These two peaks disappear for the CN r -Y (r ¼ 1.2, 1.4, 2.0) samples, implying that the melamine has been nished aer the polymerization reaction.…”
Section: Raman Spectroscopy and Ftir Spectroscopymentioning
confidence: 99%
“…7 (a-c) The normalized PL emission spectra of the CN indicate the formation of graphite structure in bulk g-C 3 N 4 . 20,45,46 The melamine has two ngerprint peaks located at around 675 cm À1 (triazine ring breathing mode) and 1558 cm À1 (NH 2 bending mode), respectively. 47,48 These two peaks disappear for the CN r -Y (r ¼ 1.2, 1.4, 2.0) samples, implying that the melamine has been nished aer the polymerization reaction.…”
Section: Raman Spectroscopy and Ftir Spectroscopymentioning
confidence: 99%
“…Time‐resolved emission spectra were carried out to gain insight into the effect of defect‐related states on tuning the radiatively relaxed transition, choosing pristine g‐C 3 N 4 (blue), CNS 0.01 (yellow), and CNS 0.05 (orange) as model samples for investigation. The emission centers of pristine g‐C 3 N 4 were located at ≈430 and 470 nm, originated from the transition of δ*→LP and π*→LP, respectively (Figure e) . Upon low‐content molecular doping (CNS 0.01 ), a new emission center at 510 nm is detected as dominant peak while the intrinsic emissions of ≈430 and 470 nm are weakened, indicating the creation of intermediate states form below the π* states during the modification process (Figure f).…”
Section: Resultsmentioning
confidence: 95%
“…To explain the tunable PL emission mechanisms of thiophene‐doped g‐C 3 N 4 , DFT calculations were performed to study the modulation electronic properties by the doping of the strong electron donor groups. Theoretical calculations indicated that the PL emission of g‐C 3 N 4 products are determined by the photoinduced electron radiative transition from CB to VB, related to the lowest unoccupied molecular orbital (LUMO) of CN bond orbitals in the π‐conjugated system, and the highest occupied molecular orbital (HOMO) of an LP in the N 2p orbitals ( Figure a), respectively . The incorporation of the thiophene‐conjugated system into the tri‐s‐triazine‐conjugated structure can efficiently relocalize the π electrons by the effect of its electron‐donating characteristics, resulting in the stronger π electron delocalization within the sp 2 domain.…”
Section: Resultsmentioning
confidence: 99%
“…In all the samples, there were two characteristic diffraction peaks positioned at 13.0° and 27.8°, with the strong characteristic peak at 27.8°, which was indexed to the (0 0 2) planes of g‐C 3 N 4 , corresponding to the interlayer‐stacking of the conjugated aromatic system, indicating that the thus‐formed nanocomposites possess layered structures . The peak intensity of our samples was obviously weaker than that of the bulk g‐C 3 N 4 , which is caused by the reduced length of interlayer periodicity . In addition, the weak diffraction peak at 13.0° was ascribed to the (1 0 0) diffraction of g‐C 3 N 4 , suggesting that the tris‐triazine units exhibit graphitic layered stacking …”
mentioning
confidence: 82%